Role of MRI in evaluation of oral cavity cancers from central India - Valecha, Jyoti; Ojha, Sandeep; Tripathi, Purva (International Journal of Medical Research and Review, 2018)
Introduction: Squamous cell carcinoma of oral cavity ranks in the top three types of all cancer in the India. The diagnosisof it is basically clinical and bioptic, preoperative imaging is crucial for tumor staging that helps to decide appropriate therapeutic strategy and indicate prognosis. Objectives: To evaluate the diagnostic accuracy of Magnetic resonance imaging (MRI) in staging of oral cavity cancers and to correlate the results with clinical and pathological data. Methodology: This was a prospective study of 60 patients of oral cavity squamous cell carcinomas (SCC) where MRI was performed preoperatively to determine the tumor staging, tumor thickness, infiltration of surrounding structures and bone invasion. These findings were correlated with final pathological staging. Results: Accurate correlation of T stages (TNM system) was obtained in 51 out of 60 cases on MRI. One lesion was classified as T2 on MRI but was found to be T4 on histopathology as MRI failed to detect subtle infiltration of the cortical bone. The accuracy of clinical data in T stage evaluation was 62 % (K- 0.470), however the MRI accuracy found to be 82 % (k 0.740). The sensitivity, specificity and accuracy of MRI in the detection of mandibular involvement were 94.1%, 60% and 81.5%, respectively. Conclusion: MRI plays an important role in the evaluation of oral cavity carcinomas. MRIaccurately demonstrates the tumor size, depth of invasion, bone marrow involvement, perineural spread and lymphnode metastasis which are essential for treatment planning.